Postharvest light-induced flavonoids accumulation in mango (Mangifera indica L.) peel is associated with the up-regulation of flavonoids-related and light signal pathway genes - Zhu, Wencan; Wu, Hongxia; Yang, Chengkun; Shi, Bin; Zheng, Bin; Ma, Xiaowei; Zhou, Kaibing; Qian, Minjie (Frontiers in Plant Science, 2023)
Flavonoids are important secondary metabolites in plants and light is a crucial environmental factor regulating flavonoids biosynthesis. However, effect of light on the different flavonoids compositions accumulation in mango and the relevant molecular mechanism still need to be clarified. In this study, green-mature fruits of red mango cultivar ‘Hongmang NO. 6’ were subjected to postharvest light treatment, and fruit peel color, total soluble solids content, total organic acid, and firmness of flesh were measured. The flavonoids metabolites profile, and the expression of flavonoids-related genes and light signal pathway genes were also analyzed. Results showed that light treatment promoted the red coloration of fruit peel, and increased the total soluble solids content and firmness of flesh. The concentration of flavonols, proanthocyanidins and anthocyanins, and expression of key flavonoids biosynthetic genes including MiF3H, MiFLS, MiLAR, MiANS, MiUFGT1, and MiUFGT3 were significantly induced by light. The MYBs regulating flavonols and proanthocyanidins, i.e. MiMYB22 and MiMYB12, as well as the key light signal pathway transcription factors (TFs) MiHY5 and MiHYH, were identified in mango. The transcription of MiMYB1, MiMYB12, MiMYB22, MiHY5 and MiHYH was up-regulated by light. Our results provide a postharvest technology to improve mango fruit appearance quality, and is helpful to reveal the molecular mechanism of light-induced flavonoids biosynthesis in mango.